Optical characterization of a manual tunable lens for eye-care applications - Salvador-Roger, Raquel; Esteve-Taboada, José J; Micó, Vicente (Applied optics. Optical technology and biomedical optics, 2024)
The popularity of focus tunable lenses has increased in the last decade. In this study we present an experimental optical characterization of a commercially available manually tunable lens to describe its behavior regarding optical aberrations, expressed in terms of Zernike coefficients, under different laboratory conditions. Measurements were performed by using a Shack-Hartmann aberrometer, and four different experiments were carried out in order to assess 1) the lens stability in time for a given temperature, 2) the temporal response of the lens, 3) the behavior of the lens when changing the room temperature, and 4) the possible influence of gravity on the lens performance according to its mounting orientation. The main conclusion we outlined states that the properties of the tunable lens stay steady over time as long as room temperature remains constant, making it a good option for ophthalmologic and optometric eye-care applications.